Endoplasmic reticulum stress impairs cardiomyocyte contractility through JNK-dependent upregulation of BNIP3. (1st December 2018) - Bozi, Luiz H.M.; Takano, Ana P.C.; Campos, Juliane C.; Rolim, Natale; Dourado, Paulo M.M.; Voltarelli, Vanessa A.; Wisløff, Ulrik; Ferreira, Julio C.B.; Barreto-Chaves, Maria L.M.; Brum, Patricia C.
Abstract: Background: Disruption of endoplasmic reticulum (ER) homeostasis is a common feature of cardiac diseases. However, the signaling events involved in ER stress-induced cardiac dysfunction are still elusive. Here, we uncovered a mechanism by which disruption of ER homeostasis impairs cardiac contractility. Methods/results: We found that ER stress is associated with activation of JNK and upregulation of BNIP3 in a post-myocardial infarction (MI) model of cardiac dysfunction. Of interest, 4-week treatment of MI rats with the chemical ER chaperone 4-phenylbutyrate (4PBA) prevented both activation of JNK and upregulation of BNIP3, and improved cardiac contractility. We showed that disruption of ER homeostasis by treating adult rat cardiomyocytes in culture with tunicamycin leads to contractile dysfunction through JNK signaling pathway. Upon ER stress JNK upregulates BNIP3 in a FOXO3a-dependent manner. Further supporting a BNIP3 mechanism for ER stress-induced deterioration of cardiac function, siRNA-mediated BNIP3 knockdown mitigated ER stress-induced cardiomyocyte dysfunction by reestablishing sarcoplasmic reticulum Ca 2+ content. Conclusions: Collectively, our data identify JNK-dependent upregulation of BNIP3 as a critical process involved in ER stress-induced cardiomyocyte contractile dysfunction and highlight 4PBA as a potential intervention to counteract ER stress-mediated BNIP3 upregulation in failing hearts. Highlights: Attenuation of ER stress prevents activation of JNK and upregulation of BNIP3, and improves cardiac function in MI rats. ER stress induces a JNK-dependent upregulation of BNIP3 ER stress-induced upregulation of BNIP3 reduces sarcoplasmic reticulum Ca 2+ content, leading to cardiomyocyte dysfunction